3D‐Printed Micro Lens‐in‐Lens for In Vivo Multimodal Microendoscopy. Issue 17 (1st March 2022) - Li, Jiawen; Thiele, Simon; Kirk, Rodney W.; Quirk, Bryden C.; Hoogendoorn, Ayla; Chen, Yung Chih; Peter, Karlheinz; Nicholls, Stephen J.; Verjans, Johan W.; Psaltis, Peter J.; Bursill, Christina; Herkommer, Alois M.; et al.
Abstract: Multimodal microendoscopes enable co‐located structural and molecular measurements in vivo, thus providing useful insights into the pathological changes associated with disease. However, different optical imaging modalities often have conflicting optical requirements for optimal lens design. For example, a high numerical aperture (NA) lens is needed to realize high‐sensitivity fluorescence measurements. In contrast, optical coherence tomography (OCT) demands a low NA to achieve a large depth of focus. These competing requirements present a significant challenge in the design and fabrication of miniaturized imaging probes that are capable of supporting high‐quality multiple modalities simultaneously. An optical design is demonstrated which uses two‐photon 3D printing to create a miniaturized lens that is simultaneously optimized for these conflicting imaging modalities. The lens‐in‐lens design contains distinct but connected optical surfaces that separately address the needs of both fluorescence and OCT imaging within a lens of 330 µm diameter. This design shows an improvement in fluorescence sensitivity of >10x in contrast to more conventional fiber‐optic design approaches. This lens‐in‐lens is then integrated into an intravascular catheter probe with a diameter of 520 µm. The first simultaneous intravascular OCT and fluorescence imaging of a mouse artery in vivo is reported. Abstract : Two‐photon 3D printing enables the development of micro‐lenses simultaneously optimized for multiple imaging modalities. The lens‐in‐lens design is incorporated into a 0.33 mm lens capable of high sensitivity fluorescence measurements in parallel with optical coherence tomography over a large depth of focus. This is demonstrated in an endoscopic probe for in vivo imaging inside the blood vessel of a mouse.